Predicting Intergroup Bias: The Interactive Effects of Implicit Theory and Social Identity - HONG, Ying-Yi (Institutional Knowledge at Singapore Management University, 2004)
This research sought to integrate the implicit theory approach and the social identity approach to understanding biases in intergroup judgment. The authors hypothesized that a belief in fixed human character would be associated with negative bias and prejudice against a maligned group regardless of the perceiver's social identity. By contrast, a belief in malleable human character would allow the perceiver's social identity to guide intergroup perception, such that a common ingroup identity that includes the maligned group would be associated with less negative bias and prejudice against the maligned group than would an exclusive identity. To test these hypotheses, a correlational study was conducted in the context of the Hong Kong 1997 political transition to examine Hong Kong Chinese's perceptions of Chinese Mainlanders, and an experimental study was conducted in the United States to examine Asian Americans' perception of African Americans. Results from both studies supported the authors' predictions.